Malaria Transmission and Fetal Growth. Issue 5928 (17th August 1974) - Macgregor, J. D.; Avery, J. G.
Abstract : In view of the known relation between infection of the maternal circulation of the placenta with Plasmodium falciparum and impaired fetal growth a study was made of the effect on birth weights of a malaria eradication campaign in the British Solomon Islands. Mean birth weights rose substantially within months of starting antimalarial operations. The increases between 1969 and 1971 averaged 252 g in babies of primigravidae and 165 g in all babies. The proportion of babies with birth weights of less than 2, 500 g fell by 8% overall and by 20% among babies of primigravidae. The adverse effect of malaria transmission on fetal growth was apparently reversible if transmission of infection in the community was interrupted up to as late as the third trimester of pregnancy. The beneficial effects of malaria eradication operations on infant survival, child development, and social attitudes in developing countries are discussed.